Lenguaje coloquial en las noticias del Diario Digital Voz Populi - Zárate Acosta, Tafanny Leonor (2021)
This research work was based on the colloquial language used by the Digital Newspaper "Voz Populi", in the cases "Marroneo UTB" and "Students fighting in the street style", with the aim of making a description of the colloquial language used by this half. The techniques that were used were through the open question interview with the owner of the medium, which allowed to know information on the topic of interest, in addition to the observation file of the audiovisual reports and a focus group to know different opinions of a professional, a student of social communication and a follower of the page of this newspaper. Throughout this case analysis, the characteristics that make up "Voz Populi" as a digital medium are exposed, and in depth the features of its language in general and the objective cases, "Marroneo UTB" and "Students fighting street style" as such. , the way they presented the reports. "Voz Populi" as Diario Digital is within the new models and standards of modern journalism in Ecuador, transcending its journalistic development, without departing from the informative approach; It was also shown that the colloquial language used by the digital communication medium goes with the personality of Mr. Jesús Mero Ormaza, owner of the Digital Newspaper “Voz Populi”.